STARTING CONDITION DALAM COLLABORATIVE GOVERNANCE PENGEMBANGAN DESA WISATA KABUPATEN BUTON - Zaitun, Zaitun; Tenri, Andi; Hisanuddin, La Ode Syaiful Islamy (Governance, 2025)
This study aims to analyze how Starting Condition in collaborative governance of tourism village development in Buton Regency. This study uses Qualitative methods, Data analysis techniques by preparing data and organizing data, reducing data and presenting data. This study uses the theory of Ansel and Gash which divides starting conditions in collaborative governance into Power Resource Knowledge Asymmetries, Incentives for and Constraints on Participation, and Prehistory of Cooperation or Conflict (initial trust level). The results of the study show that: Power Resource Knowledge between stakeholders is a problem that is often found in collaborative governance. This imbalance can lead to the dominance of stronger actors, which affects not only the decision-making process but also the results of collaboration. Likewise, Incentives for participation optimal participation is often hampered by imbalances of power, imbalances of knowledge, limited resources, and complicated bureaucratic processes. Therefore, to improve the effectiveness of collaborative governance, it is important to overcome these constraints, such as increasing the capacity of community knowledge, improving access to resources, and simplifying bureaucratic procedures, so that all actors can participate more actively in managing tourism villages. In addition, the fear of conflict that when stakeholders are interdependent, high levels of conflict can provide great benefits for collaborative governance. Policy deadlock can actually provide a strong impetus for collaborative governance, therefore high conflict is not always a barrier to collaboration. In many literatures it is explained that stakeholders see that they cannot achieve the desired goals without engaging in the collaboration process even though there are conflicting interests from other stakeholders.